Refining the Make My Day stroke prevention intervention for primary healthcare through co-creation with stakeholders - Cecilia Johnsson; Elin Jakobsson; Maria Hagströmer; Susanne Guidetti; Ann-Helen Patomella; Eric Asaba (Research Involvement and Engagement)
Abstract Objectives To describe and explore the refinement of a stroke prevention intervention and conditions for implementation in primary healthcare by utilising co-creation with stakeholders. Method This was an iterative co-creation process of five collaborative workshops engaging stakeholders; healthcare professionals (HP), and persons at risk for stroke, who participated in or delivered a stroke prevention intervention in primary healthcare. Results Through co-creation with stakeholders key components for revision were identified in the Make My Day intervention. The overall pedagogics, which was recognised as overarching, and three additional key components: the HP education, the intervention sessions, and the digital tool were identified. Moreover, the co-creation process rendered refinements of the prevention program addressing the key components representing stakeholder experiences. Refinements encompass delivering and receiving the Make My Day intervention, material ownership, and the interprofessional team. Conclusions The co-creation process revealed the importance of applying a strategic pedagogic approach in a complex intervention. The process underscored the need to augment a sense of material ownership and to improve interprofessional collaboration in primary healthcare, ultimately enhancing the intervention experience and facilitating the change process for individuals at risk of stroke. Utelising a co-creation process in this current intervention allowed for creation of refinements to the intervention optimising conditions for implementation.